Preference of urban and rural older people in Shandong Province for long-term care insurance: based on discrete choice experiment - Jin, Wenxue; Wang, Junlei; Hu, Xiaoqian (Frontiers in Public Health, 2024)
Background Severe population ageing and weak long-term care support systems has spurred China’s pilot program for long-term care insurance (LTCI). This study aimed to provide references for optimizing long-term care insurance policies in Shandong Province by measuring the preferences of urban and rural older people for LTCI. Methods Based on the discrete choice experiment, a questionnaire survey was conducted on urban and rural older people from Shandong Province. A mixed logit model was used for data analysis and the relative importance of attributes, willingness to pay, and preference heterogeneity based on residence type, number of children, chronic conditions, gender, education level and financial situation were further estimated. Results The results showed that individual premium, reimbursement rate and whose provision of home-based care can be reimbursed had a significant effect on the LTCI preference of urban and rural older people in Shandong Province. Benefit package and government subsidy lost statistical significance in full sample but played a role in certain subgroups. There were also differences in preferences for individual premium among different groups of older people. Conclusion Optimizing the policy design of long-term care insurance based on the actual needs of the older adults can help increase the utility of them and promote the smooth implementation of long-term care insurance.